Engineering Solutions for Sustainability Materials and Resources II - Fergus, Jeffrey; Mishra, Brajendra; Anderson, Dayan; Allyn Sarver, Emily; Neelameggham, Neale; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
With impending and burgeoning societal issues affecting both developed and emerging nations, the global engineering community has a responsibility and an opportunity to truly make a difference and contribute. The papers in this collection address what materials and resources are integral to meeting basic societal sustainability needs in critical areas of energy, transportation, housing, and recycling. Contributions focus on the engineering answers for cost-effective, sustainable pathways; the strategies for effective use of engineering solutions; and the role of the global engineering community. Authors share perspectives on the major engineering challenges that face our world today; identify, discuss, and prioritize engineering solution needs; and establish how these fit into developing global-demand pressures for materials and human resources.
Keywords: Materials; Sustainability; Materials -- Analysis; Materials Engineering; Sustainability; Characterization and Analytical Technique